Study of Two-Dimensional Phase Objects by Diffraction Focusing of Cylindrical X-Ray Wave on a Superlattice With Variable Period - Levonyan, L. V.; Manukyan, H. M.
The possibility of studying the internal structure of two-dimensional phase objects at diffraction focusing of X-ray cylindrical wave is investigated. As a crystal analyzer a superlattice with a period, variable along the axis of the cylinder was used in symmetric Laue geometry case. It is shown that by moving the phase object along the directions of the diffraction vector and the axis of the cylinder and recording the entire map of the obtained data, one can restore the additional phase of the wave, acquired in the phase object which in the end will afford an opportunity to restore the internal structure of the corresponding section of the phase object.
Keywords: Physics; Optics